Pravni vidik sodelovanja med šolo (učitelji) in starši v osnovni šoli - Grafenauer Ekart, Živa (Vzgoja in izobraževanje, 2022)
Numerous studies have found positive effects of school-home collaboration, but this is not the only reason for that collaboration. Namely, in the article we found out that, in accordance with the Constitution of the Republic of Slovenia, international treaties ratif ied and published by the Republic of Slovenia, as in accordance with applicable legislation in the Republic of Slovenia parents have the right and dutyto decide on the education of their children. The main purpose of cooperation between school and home is the best interests of the child. The article provides an expert overview of legal acts that regulate the cooperation between school and parents and the dilemmas that arise in this f ield. Mediation can be a prorer way to reslove disputes between school and parents.
Keywords: medosebna komunikacija; osnovna šola; parents; primary school; Slovenija; sodelovanje; starši; šolska zakonodaja; Ustava RS; vzgoja in izobraževanje